การเปลี่ยนแปลงของผลคะแนนการทดสอบทางการศึกษาระดับชาติขั้นพื้นฐาน (O-NET) ของนักเรียนชั้นประถมศึกษาปีที่ 6 จังหวัดลพบุรี และอ่างทอง: The Variance of Ordinary National Educational Test Scores (O-NET) of Prathomsuksa 6 Students Studying in Lopburi and Ang-Thong Province, Thailand - Chawianghong, Bunyanuch; chaloeywares, neti (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The objectives of this research study were 1) to investigate the variance of the Ordinary National Educational Test Scores (O-NET) of Prathomsuksa 6 students studying in Lopburi and Ang-Thong province and 2) to explore the methods used in improving the Ordinary National Educational Test Scores (O-NET). The research methods were 2 stages which were 1) investigate O-NET of Prathomsuksa 6 students and 2) interviewed the educational supervisors, the administrators of the schools, teachers and investigated the school performance reports in the point of the strategies used in improving O-NET of Prathomsuksa 6 students. The research instruments were records on test scores and interviewed scripts. Data were analyzed by using frequency, percentage, mean, standard deviation and content analysis. The findings showed that: The research results revealed that 1) the variance of O-NET of Prathomsuksa 6 students studying in Lopburi and Ang-Thong province tend to be higher and 2) guidelines suggested in improving O-NET of Prathomsuksa 6 students were covering all indicators when teaching, applying different teaching methods, stimulating the students by using the previous O-NET Test before the real testing at least one month or more and providing extra classes during the morning time before class , lunch time, and in Moderate Class, More Knowledge hours.